Training on Strengthening the Profile of Pancasila Students at TK ABA - Pramudyani, Avanti Vera Risti; Aulia, Syifa Siti (Universitas Muhammadiyah Surakarta, 2024)
Pancasila, Indonesia's national philosophy, is essential in creating a good and quality society. The implementation of the Independent Curriculum in PAUD Pancasila is applied with the concept of the Strengthening the Profile of Pancasila Students (P5) Project. However, many ECCE institutions, especially ABA Danunegaran Kindergarten, still need help implementing. Through community service activities carried out by the team, it is hoped that teachers, students, and parents will know and understand the P5 implemented by integrating Pancasila values into the learning process in schools to cultivate moral, ethical, and social responsibility. Training activities are conducted offline or face-to-face using lectures, discussions, and practice methods. The training is carried out with two terms: Tuesday and Thursday, August 22 and 24, 2023 and term 2, Thursday - Friday, October 4 - 5, 2023. In the implementation, the team consisted of lecturers and five students from the PG PAUD and PPKN Study Programs. Community service results in increased knowledge and understanding of P5 in the learning process, which is packed with fun activity projects, namely playing educational games. The output of the activity was in the form of two articles in journals, national oral seminars, articles in the mass media, videos of activities uploaded to the YouTube page and IPR games.